PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) DALAM MEMBACA PERMULAAN SISWA KELAS II SDN 004 BATURIJAL HULU KECAMATAN PERANAP - Aida Nursanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This research was motivated by the low ability of students to read at the beginning, so the researchers applied the SAS method in order to help students who still had difficulty reading. This study aims to determine the difference between the pretest and posttest by applying the synthetic analytical structural method (SAS) in reading the beginning of grade II elementary school students and to determine the increase in the pretest and posttest in reading the beginning of students. This type of research is a type of pretest-posttest one group pre-experimental design, which is an experiment that is only carried out in one group, without comparison. This research was carried out in class II SDN 004 Baturijal Hulu, Peranap sub-district with a total of 29 students. Based on the research results, it was found that the average value of reading ability before being treated (pretest) was 51.68 while the average value of reading ability after treatment (posttest) was 88.65 and the average value of normality gain was 0.76 which including the high category and the results of hypothesis testing using t-test with t = 47.191 and t table = 2.045, it is concluded that t count> t table, then reject H0 means significant. This means that there is a significant increase in pre-test reading in grade II students between before (pretest) and after (posttest) applying the Synthetic Structural Analytical (SAS) method.